# C program to remove the brackets from a given input.

CServer Side ProgrammingProgramming

## Problem

Let’s create a simplified expression by removing brackets from the expressions.

## Solution

### Example 1

Input: A string expression with bracket is as follows:
(x+y)+(z+q)
The output is as follows:
x+y+z+q

### Example 2

The input is as follows:
(x-y+z)-p+q
The output is as follows:
x-y+z-p+q

## Algorithm

Refer an algorithm to remove the brackets from a given input.

Step 1: Declare and read the input at runtime.

Step 2: Traverse the string.

Step 3: Copy each element of the input string into new string.

Step 4: If anyone parenthesis is encountered as an element, replace it with empty space.

## Example

Following is the C program to remove the brackets from a given input −

#include<stdio.h>
int main(){
int i=0,c=0,j=0;
char a,b;
printf("\nEnter the string :");
scanf("%s",a);
while(a[i]!='\0'){
if((a[i]=='(') && (a[i-1]=='-')){
(c=0)?j=i:j=c;
while(a[i]!=')'){
if(a[i+1]=='+')
b[j++]='-';
else if(a[i+1]=='-')
b[j++]='+';
else if(a[i+1]!=')')
b[j++]=a[i+1];
i++;
}
c=j+1;
}
else if(a[i]=='(' && a[i-1]=='+'){
(c==0)?j=i:j=c;
while(a[i]!=')'){
b[j++]=a[i+1];
i++;
}
j–;
c=j+1;
}
else if(a[i]==')'){
i++;
continue;
} else {
b[j++]=a[i];
}
i++;
}
b[j]='\0';
printf("%s",b);
return 0;
}

## Output

When the above program is executed, it produces the following output −

Enter the string:(x+y)-z
x+y-z